Multi-Agent-Based Voltage Regulation Scheme for High Photovoltaic Penetrated Active Distribution Networks Using Battery Energy Storage Systems - Yongxi Zhang; Ke Meng; Fengji Luo; Hongming Yang; Jiahua Zhu; Zhao Yang Dong (IEEE Access, 2020)
This paper develops a distributed voltage regulation scheme for high Photovoltaic (PV) penetrated distribution networks by utilizing battery energy storage (BES) units. In this study, multiple BES units form a multi-agent network, in which each BES unit acts as an individual agent and can communicate with its neighbors to perform the distribution network's voltage regulation in a cooperative manner. To cope with the uncertainties of PV power and load demand, a receding horizon-based approach is proposed, where BES control decisions for regulating bus voltages are updated with the update of the system's operational conditions (PV power, load, etc.). An efficient solving method - Distributed Alternating Direction Method of Multipliers Algorithm (D-ADMM) is applied to solve the proposed model under a colored network, where the BES agents with the same color synchronously update their states. Case studies are conducted on modified IEEE benchmark systems to validate the performance of the proposed method.